"Arena" di Dalam Perilaku Pencarian Informasi untuk Mendapatkan Lagu: Pendekatan Grounded Theory - Putra, Riyan Adi; Laksmi, Laksmi; Wijayanti, Luki (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2021)
Songs are the simplest things for each individual to like. With the development of information technology, songs have also changed from analog to digital. This causes a song that is a copyrighted work to be easily obtained. Therefore, in this study, we want to discuss the information-seeking behavior of the society to get the song. In this research, the theory of information-seeking behavior will be placed with the theory of actions or habits put forward by Bourdieu, namely capital, habitus, and "arena". This research aims to understand the action in obtaining the song from the perspective of information-seeking behavior theory and Bourdieu theory. Besides, it is hoped that this research can also make new contributions regarding the theory of information behavior which can be seen from a socio-cultural point of view. The method used in this research is grounded theory of systematic design types with a qualitative approach. The results of this study explain that the entire process of searching for information to get a song is an "arena", where there are battles that are formed through their habitus as an effort to balance capital between them. This study suggests clear law enforcement in Indonesia regarding copyright and the need to look at a scientific discipline.